2012
DOI: 10.2174/1874312901206010170
|View full text |Cite
|
Sign up to set email alerts
|

Sicca Symptoms and their Association with Chronic Rhinosinusitis in a Community Sample

Abstract: Objective:To determine associations between sicca symptoms, chronic rhinosinusitis (CRS) symptoms and asthma in a community survey.Methods:Data was obtained from the Spring 2009 South Australian Health Omnibus Survey which sampled, via interviewer administered questionnaire, 3007 individuals aged 15 years and over whose socio-demographic distribution corresponded to South Australian population estimates. Respondents were asked a range of questions relating to the presence of persistent dry eyes or dry mouth, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…While xerostomia and xerophthalmia are often attributed to environmental factors (temperature-controlled air, screen handling), drugs (contraceptives, beta-blockers, psychotropic drugs, etc. ), and systemic diseases such as diabetes mellitus or thyroid disorders, approximately 2 % of the adult population suffers from pSS [1][2][3][4][5], which represents the most important rheumatic disorder affecting the head and neck [6]. The slowly progressive clinical course and the lack of symptom specificity often dramatically prolong the time to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While xerostomia and xerophthalmia are often attributed to environmental factors (temperature-controlled air, screen handling), drugs (contraceptives, beta-blockers, psychotropic drugs, etc. ), and systemic diseases such as diabetes mellitus or thyroid disorders, approximately 2 % of the adult population suffers from pSS [1][2][3][4][5], which represents the most important rheumatic disorder affecting the head and neck [6]. The slowly progressive clinical course and the lack of symptom specificity often dramatically prolong the time to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the 'natural' glandular atrophy that occurs in the elderly, environmental factors such as temperaturecontrolled air, screen handling, ozone, dust, solvent vapours, contraceptives, beta-blockers, and psychotropic drugs are known to induce sicca symptoms [1,2]. A recent study demonstrated an association with chronic rhinosinusitis [3]. Diabetes mellitus, thyroid diseases, and autoimmunity, on the other hand, consistently caused xerostomia/xerophthalmia [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have provided controversial conclusions regarding the predisposition of patients with SS toward CRS, and studies evaluating the relationship between SS and CRS are scant [3,7]. To the best of our knowledge, this is the first population-based study with long-term follow-up to investigate the risk of CRS in patients with SS.…”
Section: Discussionmentioning
confidence: 99%
“…Sjögren’s syndrome (SS) is a chronic autoimmune disorder characterized by the lymphocytic infiltration of exocrine glands, particularly the salivary and lacrimal glands, which can lead to xerostomia and keratoconjunctivitis sicca [3,4,5]. In addition, SS may involve dryness and chronic inflammation of the sinonasal mucosa, which may cause CRS [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation